Framing a metabolic risk. Sviluppare un framework metodologico per l’analisi e il monitoraggio del potenziale di resilienza dei wastescape in contesti urbani critici multirischio - Amenta, Libera; Attademo, Anna; Bosone, Martina; De Toro, Pasquale; Russo, Michelangelo (Contesti. Città, territori, progetti, 2026)
Urban multi-risk systems are characterised by systemic vulnerability and poor resilience to crises. Starting from an analysis of the relationship between the concepts of resilience and metabolic risk, this study proposes a methodological framework for analysing, evaluating and mapping the resilience potential of wastescapes in multi-risk urban contexts, characterised by unexpressed resource capital (matter, nature, space). The framework has the dual value of being an assessment tool and a support in guiding the definition of regenerative strategies for wastescapes in the perspective of the circular economy model applied to urban metabolism, in order to improve the resilience of cities and communities starting from the potential of places.